Thermal Conductivity Enhancement of Aluminium Oxide Nanofluid in Ethylene Glycol - Khamisah, Abdul Hamid; Azmi, W. H.; R., Mamat; N. A., Usri (Trans Tech Publications, Switzerland, 2014)
Nanofluids are the new coolant fluid that has been widely investigates due to its ability to improved heat transfer better than conventional heat transfer fluid. The need to study the nanofluid properties has been increased to provide better understanding on nanofluid thermal properties and behavior. This study presents the measurement analysis on thermal conductivity enhancement of Al2O3 nanoparticles dispersed in ethylene glycol. The nanofluids are prepared using two step method for volume concentration range from 1.0 % to 4.0 %. The thermal conductivity measurement of the nanofluid is performed by KD2 Pro Thermal Properties Analyzer at working temperature range from 30 °C to 80 °C. The maximum enhancement in thermal conductivity is 21.1 % at volume concentration of 2.0 % and temperature of 70 °C. The results show that the thermal conductivity increases with the increase of nanofluid concentration and temperature. Also, the nanofluid shows enhancement in thermal conductivity compare to the base fluid.